Translation of pronominal forms of address in for whom the bell tolls - María José Luzón Marcos (Pragmalingüística)
The English system of personal pronouns lacks the distinction between polite and familiar second person forms, which is represented in Spanish by the opposition between "tú" and "usted". In For whom (he Bell Tolls Hemingway resorts to the Middle English distinction between "thou" and "you" in order to reflect the social and personal relationships of the characters. However, in this work "thou" and "you" are not used as exact equivalents of "tú" and "usted". Forms of address are basic elements in the communicative, pragmatic and semiotic dimensions of discourse; therefore the translator must analyst their functions in these dimensions in order 10 produce an adequate translation. In this paper we examine some examples of translation of "thou" and "you" to find out whether the linguistic item used in the target text has the same function!,\ and brings about the same effects in the translation as those of the personal pronoun in the source text.